ANALISIS PEMAHAMAN MATEMATIS SISWA MENGGUNAKAN MACROMEDIA FLASH DI KELAS VIII SMP NEGERI 3 LANGSA - Lailissaadah (Jurnal Dimensi Matematika, 2022)
This research is motivated by the low level of students' understanding of mathematics, especially on cubes and blocks. This study aims to determine the level of students' mathematical understanding by using the help of technology-based learning media, namely Macromedia Flash. This research is a Classroom Action Research (CAR). This research was conducted in three cycles. The subjects in this study were class VIII/5 SMP Negeri 3 Langsa, totaling 30 students, while the object of this research was students' mathematical understanding using Macromedia flash. The instruments used in this study were tests, observations and interviews. The data were analyzed using the percentage formula. The results showed that there was an increase in the level of classical student learning outcomes in the first cycle amounted to 57%, and in the second cycle increased to 67%, and in the third cycle increased to 83%. The author analyzed the results of the cycle test to determine the level of students' mathematical understanding with the level of mathematical understanding in the first cycle 57%, in the second cycle 67%, in the third cycle 83%. From the percentage results above, it shows that each cycle there is an increase in the mathematical understanding of the students of class VIII/5 SMP Negeri 3 Langsa, especially on cubes and blocks. From the results of this study, it can be concluded that the application of Macromedia Flash can improve the mathematical understanding of class VIII/5 students of SMP Negeri 3 Langsa.